On the escape process during phase inversion of an emulsion - Klahn, J.K; Janssen, J.J.M; Vaessen, G.E.J; de Swart, R; Agterof, W.G.M (Colloids and surfaces. A, Physicochemical and engineering aspects, 2002)
This paper deals with a phenomenon which plays an important role in the phase inversion process of emulsions. This process is governed by the interplay of coalescence of droplets, often leading to double emulsions, and the escape of those internal droplets. The latter process retards the inversion process. Coalescence has been the subject of many studies, contrary to the escape event. This paper addresses the escape process both theoretically and experimentally. The model developed analyses the rate of the escape of internal droplets from the mother droplet via a coalescence process, where the internal flow, as generated by the external flow, generates the viscous force for coalescence. Incomplete mixing in the droplet has been assumed. Experimental data on the escape rate of oil droplets from O/W/O emulsions have been analysed using a Computational Fluid Dynamics approach, where the model as indicated above has been incorporated. Experimental data and simulations compare very well. Data have been compared on varying the size of the inner droplets and the rotational speed of the vessel where the double emulsion has been formed and where the escape took place.